Kecerdasan Emosional Dan Mental Terhadap Pengambilan Keputusan Dalam Bertransaksi Trader Forex (Studi Kasus pada Pelaku Investasi di Telegram Tahun 2022) - Dafano Sefdaeniyo; N Rachma; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study purpose to determine and analyze emotional and mental intelligence in making decisions in trading forex traders in the telegram group of 75 samples, with a purposive sampling technique. The data used is primary data using a questionnaire instrument. The data analysis technique used was multiple linear regression analysis. The results showed that emotional and mental intelligence simultaneously and partially significantly influence decision making in Forex trader transactions.  Keywords: Emotional Intelligence, Mental and Decision Making